The Influence of Voluntary Disclosure, Independent Commissioners and Information Asymmetry on Cost of Debt in Metal Sub-Sector Manufacturing Companies Listing on the IDX for the 2013-2018 Period: Pengaruh Voluntary Disclosure, Komisaris Independen Dan Asimetri Informasi Terhadap Biaya Hutang (Cost Of Debt) Pada Perusahaan Manufaktur Sub Sektor Logam Yang Listing Di BEI Periode 2013-2018 - Khoiri, Amalia; Sriyono, Sriyono (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to examine the effect of voluntary disclosure, independent commissioners and information asymmetry on the cost of debt. The approach used in this study is a quantitative approach. The population used in this study is the company. The sampling technique used purposive sampling method. The sample in the study was 12 companies listed on the IDX for the period 2013-2018. The data used in this study is secondary data taken from the Indonesia Stock Exchange. Data analysis uses Eviews 10 analysis with the aim of testing voluntary disclosure, independent commissioners, and information asymmetry on the cost of debt. The results of this study indicate that voluntary disclosure has a significant effect on the cost of debt, independent commissioners have no significant effect on the cost of debt, information asymmetry has a significant effect on the cost of debt, and voluntary disclosure, independent commissioners and information asymmetry have a joint effect on the cost of debt.